The moderating effects of the government support and religious obligations on the relationship between service quality, knowledge and awareness of islamic banking system and the intention to subscribe the system in Libya - Omar, Khairi Mohamed (2015)
This study investigates the moderating effects of both the government support and religious obligations on the relationship of the service quality of CARTER’S model, knowledge and awareness of the Islamic banking system towards the intention to subscribe to the Islamic banking system in the Libyan banking sector. The study looks into the potential causes behind the delay in implementing the full-fledged Islamic banking system in Libya. The study reports the results of the surveys that were conducted among Libyan bank clients/customers. Using the primary data collection method, 384 questionnaires were distributed to the targeted respondents comprising Libyan Islamic banking subscribers and conventional banks from three main states in Libya. Only 226 (58.9 %) questionnaires were returned and analyzed using Structural Equation Modeling (SEM). The study proposed two direct relationships and two moderating effects in the structural model. The findings revealed that government support and religious obligations were significant predictors of behavioral intention to subscribe to the Islamic banking system where the significant influence of the overall service quality dimensions of the CARTER model and knowledge and awareness of Islamic banking in the Libyan context fund existed. The study supported the premises of the CARTER model confirming the importance of government support for any successful strategy implementation planning. These findings, therefore, strongly suggest that the CARTER model should be developed prior to any strategy implementation planning. The findings also indicated that it (CARTER model) is a valid model in predicting customer behavioral intention.